Chemical Exfoliation of Black Phosphorus for Nanoelectronics Applications. (8th May 2017) - Min, Misook; Saenz, Gustavo A.; Qiu, Gang; Charnas, Adam; Ye, Peide; Kaul, Anupama B.
ABSTRACT: Chemically exfoliated two-dimensional (2D) materials have shown promise in a variety of applications such as thin film transistors and photovoltaic devices. Here, we present a scalable method for preparing black phosphorus membranes via direct liquid-phase exfoliation of the bulk crystal in organic solvents. The black phosphorus sheets are characterized by Raman and Photoluminescence (PL) spectroscopy, and optical microscopy. The properties of these chemically exfoliated black phosphorus was compared to mechanically exfoliated nanomembranes. The liquid-phase exfoliation nonetheless yields the potential for large-area scalability. Our results highlight the important aspects of forming solution dispersions of 2D black phosphorus which can subsequently be the stepping stone for future work on the ink-jet printing of such dispersions over a wide range of substrates.